2021
DOI: 10.1186/s12866-021-02171-9
|View full text |Cite
|
Sign up to set email alerts
|

Defining the temporal evolution of gut dysbiosis and inflammatory responses leading to hepatocellular carcinoma in Mdr2 −/− mouse model

Abstract: Background Emerging evidence implicates the gut microbiome in liver inflammation and hepatocellular carcinoma (HCC) development. We aimed to characterize the temporal evolution of gut dysbiosis, in relation to the phenotype of systemic and hepatic inflammatory responses leading to HCC development. In the present study, Mdr2 −/− mice were used as a model of inflammation-based HCC. Gut microbiome composition and function, in addition to serum LPS, serum cytokines/chemokines and intrahepatic infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Alterations in gut microbiota composition are associated with hepatic inflammatory diseases and may play a contributory role in hepatic carcinogenesis (32). Dysbiotic gut microbiota composition leads to increased hepatic exposure with gutderived microbiota-associated molecular patterns (MAMPs) that include lipopolysaccharides (LPS), a cell wall component of Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in gut microbiota composition are associated with hepatic inflammatory diseases and may play a contributory role in hepatic carcinogenesis (32). Dysbiotic gut microbiota composition leads to increased hepatic exposure with gutderived microbiota-associated molecular patterns (MAMPs) that include lipopolysaccharides (LPS), a cell wall component of Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial compounds reach the liver via the portal blood flow and are eliminated by Kupffer cells under normal conditions (33). In a mouse model, LPS levels increase during the course of chronic liver disease fostering proinflammatory responses in the periphery and in the liver (32,34). Plasma LPS concentrations correlate with the degree of liver dysfunction (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…While it has long been thought that gut microbiota dysbiosis precedes the development of HCC, this causal relationship has not been explored in depth until more recently. Behary, Raposo et al recently found, before HCC progression, that gut microbiota dysbiosis is in tandem with early onset liver injury that is followed by an LPS-dependent Th1-and Th17-mediated cytokine response [308]. Further investigation should determine whether gut microbiota dysbiosis is a cause or consequence in the liver injury preceding HCC.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 98%
“…Bile acids and other regulatory molecules have been shown to induce the activation of the NLRP3 inflammasome ( 153 ). This causes the secretion of IL-1β, thus leading to transinflammatory liver injury and playing a role in reactive cholangiocyte inflammation in patients with PSC ( 154 ). In PSC mouse models fed with 3, 5-dioxy-carboxyl, 1, 4-dihydrogen collidine (DDC) and in human PSC, NLRP3 inflammasomes are increased in reactive bile duct cells, leading to IL-18 secretion and epithelial functional barriers of bile duct cells, thereby affecting the development of bile duct disease ( 155 ).…”
Section: Inflammasomes and Pyroptosis In Aildsmentioning
confidence: 99%